Glass photoresist, preparation method of glass photoresist and femtosecond laser preparation method

By using glass photoresist prepared by acrylic-based polysilsesquioxane and acrylate, combined with photocuring and heat treatment technology, the problem of difficulty in achieving high precision and high temperature sintering limitations in the existing technology is solved. Achieve high-quality silica micro-nano glass manufacturing.

CN119472169AInactive Publication Date: 2025-02-18深圳光子传感科技有限公司
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411385853.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2025-02-18
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing silica additive printing technology is difficult to achieve high-precision three-micron nanoscale structural printing, and the high-temperature sintering process limits the integrated application of silica glass.

Method used

A glass photoresist including acrylic polysilsesquioxane and acrylate is provided, prepared by heating and mixing method, and photocuring is performed using a photocuring device to form a glass monomer polymer crosslinking structure. The organic components in the crosslinked precursor are then decomposed by heat treatment to achieve the manufacturing of high-quality silica micro-nano glass.

Benefits of technology

The printing accuracy of silica glass is improved, the limitation of high-temperature sintering is avoided, and high-quality silica micro-nano glass manufacturing is achieved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119472169A_ABST
    Figure CN119472169A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of photoresist, in particular to glass photoresist, a preparation method of the glass photoresist and a femtosecond laser preparation method of an optical fiber end face micro-nano glass structure. The glass photoresist is prepared from acrylic polysilsesquioxane and acrylic ester, glass photoresist is arranged on a preset surface; photocuring equipment is adopted to carry out photocuring on the glass photoresist, so that the glass photoresist forms a cured structure; and performing heat treatment on the cured structure. Compared with the prior art, the glass photoresist different from the traditional silicon dioxide loaded glass photoresist is obtained, the problem that the traditional silicon dioxide additive printing technology is limited by the size of silicon dioxide nanoparticles is solved, and printing of a glass monomer polymerization cross-linked structure with the characteristic size exceeding the diffraction limit is achieved; organic components in the cross-linked precursor are effectively decomposed through heat treatment, and manufacturing of the optical fiber end face integrated high-quality silicon dioxide micro-nano glass is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of photoresist technology, and in particular to glass photoresist, a method for preparing glass photoresist, and a femtosecond laser preparation method for a micro-nano glass structure at an optical fiber end face. Background Art

[0002] As an important inorganic material, silica glass has excellent mechanical strength, optical properties, heat resistance and corrosion resistance, and has broad application prospects in MEMS sensing, micro-optical imaging and optoelectronic chip integration. However, due to the inherent brittleness and structural stability of silica glass, it has always been a challenge to manufacture silica glass integrated with the end face of an optical fiber with three micro-nano structures.

[0003] Common silica additive printing technologies include stereolithography and digital photoprinting. Although they can achieve three-dimensional manufacturing of silica glass, these technologies rely on photoresist materials loaded with silica nanoparticles, and the characteristic size of the printed structure is affected by the size of the silica nanoparticles. The resolution is usually limited to tens of microns and submicrons, and the printing accuracy is difficult to improve. In addition, in order to achieve the structural transformation of discrete silica nanoparticles to continuous silica, these methods require high-temperature treatment for several days in a vacuum or inert atmosphere, with sintering temperatures as high as thousands of degrees, which exceeds the melting point of many key semiconductor substrate materials (including optical fibers), thus limiting the integrated application of silica glass. Summary of the invention

[0004] In view of the shortcomings of the prior art, the present application provides a glass photoresist, a method for preparing a glass photoresist, and a femtosecond laser preparation method for a micro-nano glass structure on the end face of an optical fiber, which can improve the accuracy of printing silica glass.

[0005] In order to solve the above technical problems, a technical solution adopted in the present application is: to provide a glass photoresist, including acrylic polysilsesquioxane and acrylate.

[0006] In order to solve the above technical problems, a technical solution adopted in the present application is: to provide a glass photoresist preparation method, which is used to prepare the glass photoresist as described in the above technical solution, including mixing acrylic polysilsesquioxane and acrylate and stirring to obtain a first mixture; adding a photoinitiator to the first mixture and stirring to obtain the glass photoresist.

[0007] In a specific embodiment, the mixing of acrylic polysilsesquioxane and acrylic ester and stirring comprises mixing acrylic polysilsesquioxane and acrylic ester in a mass ratio of (5 to 20):1 and stirring for 5 to 15 minutes.

[0008] In a specific embodiment, the mass ratio of the photoinitiator to the first mixture is 1:(25-100).

[0009] In a specific embodiment, adding a photoinitiator to the first mixture and stirring to obtain the glass photoresist includes adding the photoinitiator to the first mixture in an environment isolated from ultraviolet rays and stirring for 12 to 24 hours to obtain the glass photoresist.

[0010] In a specific embodiment, the stirring for 12 to 24 hours to obtain the glass photoresist includes heating to 50 to 70° C. and maintaining for 6 to 12 hours with continuous stirring; and continuing stirring for 6 to 12 hours after stopping the heating to obtain the glass photoresist.

[0011] In order to solve the above technical problems, a technical solution adopted in the present application is: to provide a femtosecond laser preparation method for a micro-nano glass structure on the end face of an optical fiber, including using a glass photoresist as described in the above technical solution; setting the glass photoresist on a preset surface; using a photocuring device to photocure the glass photoresist so that the glass photoresist forms a cured structure; and heat treating the cured structure.

[0012] In a specific embodiment, setting the glass photoresist on a preset surface includes setting the glass photoresist on an optical fiber end face; using a photocuring device to photocuring the glass photoresist includes: using a femtosecond laser device to photocuring the glass photoresist, and the power of the femtosecond laser is less than or equal to 5mW.

[0013] In a specific embodiment, the heat treatment of the cured structure includes heating the glass photoresist to 600-800°C at a rate of 1-3°C / min and keeping the temperature constant for 1-3 hours; and cooling the glass photoresist to room temperature at a rate of 3-7°C / min.

[0014] In a specific embodiment, after forming the glass photoresist into a solidified structure and before heat-treating the solidified structure, the process further includes washing the preset surface with isopropyl alcohol.

[0015] The beneficial effect of the present application is that compared with the prior art, the glass photoresist, the method for preparing the glass photoresist and the femtosecond laser preparation method of the micro-nano glass structure on the end face of the optical fiber provided by the present application provide a glass photoresist including acrylic polysilsesquioxane and acrylate and a preparation method thereof, which can prepare a glass photoresist different from the traditional silica load by a heating mixing method, and use a photocuring device to photocure the glass photoresist, so that the printed cured structure can achieve the printing of a glass monomer polymerization cross-linked structure with a characteristic size beyond the diffraction limit, and then effectively decompose the organic components in the cross-linking precursor through heat treatment, thereby realizing the manufacture of high-quality silica micro-nano glass. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 It is an electron microscope image of multiple embodiments of the femtosecond laser preparation method of the optical fiber end face micro-nano glass structure of the present application;

[0017] Figure 2 This is a structural statistical diagram of high temperature stability test of a solidified structure obtained by the femtosecond laser preparation method of the optical fiber end face micro-nano glass structure of the present application;

[0018] Figure 3 This is a schematic diagram of the first process of the glass photoresist preparation method of the present application;

[0019] Figure 4 It is a schematic block diagram of the second process of the glass photoresist preparation method of the present application;

[0020] Figure 5 It is a schematic flow chart of the femtosecond laser preparation method of the optical fiber end face micro-nano glass structure of the present application;

[0021] Figure 6 It is a schematic flowchart of the heat treatment process of the femtosecond laser preparation method of the optical fiber end face micro-nano glass structure of the present application. DETAILED DESCRIPTION

[0022] In the present invention, the terms "disposed", "provided with", and "connected" should be understood in a broad sense. For example, it can be a fixed connection, a detachable connection, or an integral structure; it can be a mechanical connection, or an electrical connection; it can be a direct connection, or an indirect connection through an intermediate medium, or it can be an internal connection between two devices, elements, or components. For those of ordinary skill in the art, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.

[0023] The orientation or position relationship indicated by the terms "center", "longitudinal", "lateral", "length", "width", "thickness", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside", etc. are based on the orientation or position relationship shown in the drawings and are only for the convenience of describing the present application and simplifying the description, and do not indicate or imply that the referred device or element must have a specific orientation, be constructed and operated in a specific orientation, and therefore should not be understood as a limitation on the present application.

[0024] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include at least one of the features. In the description of this application, the meaning of "plurality" is at least two, such as two, three, etc., unless otherwise clearly and specifically defined.

[0025] In addition, some of the above terms may be used to express other meanings in addition to indicating orientation or positional relationship. For example, the term "on" may also be used to express a certain dependency or connection relationship in some cases. For those skilled in the art, the specific meanings of these terms in the present invention can be understood according to specific circumstances.

[0026] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0027] As an important inorganic material, silica glass has excellent mechanical strength, optical properties, heat resistance and corrosion resistance, and has broad application prospects in MEMS (Micro-Electro-Mechanical System) sensing, micro-optical imaging and optoelectronic chip integration. However, due to the inherent brittleness and structural stability of silica glass, it has always been a challenge to manufacture silica glass integrated with the end face of an optical fiber with a three-micro-nano structure.

[0028] Currently, silica additive printing technology is usually used, which can include stereolithography and digital light printing. Although silica additive printing technology can achieve three-dimensional manufacturing of silica glass, due to the size limitation of silica nanoparticles, the characteristic size resolution of the printed structure is usually limited to tens of microns and sub-microns, making it difficult to break through to higher precision.

[0029] In addition, the silica additive printing technology also relies on the photoresist material loaded by silica nanoparticles. In order to achieve the structural transformation of discrete silica nanoparticles into continuous silica, it is necessary to carry out high-temperature treatment for several days in a vacuum or inert atmosphere, with the sintering temperature reaching thousands of degrees. However, the excessively high sintering temperature exceeds the melting point of many important semiconductor substrate materials (including optical fibers), which greatly limits the integrated application of silica glass.

[0030] In order to improve or solve the above technical problems, the inventors of the present application have proposed at least the following embodiments after long-term research.

[0031] The embodiment of the present application provides a glass photoresist, which is also called photoresist, and refers to a thin film material whose solubility changes when exposed to ultraviolet light, electron beam, ion beam, X-ray, etc. It is used as an anti-corrosion coating material during the photolithography process.

[0032] The glass photoresist provided in this embodiment may include acrylic polysilsesquioxane and acrylate, which are usually liquid at room temperature and easy to store and mix. When a photoinitiator is added and ultraviolet light is applied, acrylic polysilsesquioxane can undergo a photocuring reaction with acrylate to produce silicon dioxide micro-nano glass (R-SiO2).

[0033] Since acrylic polysilsesquioxane and acrylate are both liquid, they can form a uniform mixture after mixing, and can also form a uniform structure when used to print glass. The size of acrylic polysilsesquioxane and acrylate molecules in the mixed glass photoresist is much smaller than that of silica nanoparticles. The silica micro-nano glass printed by acrylic polysilsesquioxane and acrylate participating in the reaction is extremely high in precision and is not limited by the size of silica nanoparticles. In addition, the reaction of acrylic polysilsesquioxane and acrylate does not require sintering in a high-temperature environment, and can be applied to most substrate materials.

[0034] See also Figure 3 , Figure 3 1 is a schematic diagram of the first process of the method for preparing glass photoresist of the present application. The embodiment of the present application provides a method for preparing glass photoresist, which is used to prepare the glass photoresist as described in the above embodiment. The method for preparing glass photoresist may include the following steps:

[0035] S100: Mixing acrylic polysilsesquioxane and acrylic ester and stirring to obtain a first mixture.

[0036] In the process of preparing the glass photoresist, the acrylic polysilsesquioxane and the acrylate may be mixed and stirred first, so that the two can be mixed evenly to obtain a first mixture.

[0037] S200: Adding a photoinitiator to the first mixture and stirring to obtain a glass photoresist.

[0038] Then, a photoinitiator is added to the first mixture, and the mixture is stirred to obtain a glass photoresist.

[0039] Among them, the photoinitiator is also called photosensitizer or photocuring agent, which can absorb energy of a certain wavelength in the ultraviolet region (250-420nm) or the visible region (400-800nm), thereby generating free radicals, cations, etc., which can initiate the polymerization of monomers and cross-linking and curing compounds. In this embodiment, the photoinitiator can be DBMP (2-benzyl-2-(dimethylamino)-4'-morpholinobutylphenyl ketone), and its chemical formula is C 23 H 30 N2O2. DBMP can be added to the first mixture to form free radicals through free radical chain polymerization under ultraviolet irradiation to initiate the reaction between acrylic polysilsesquioxane and acrylate.

[0040] The photocuring reaction formula of acrylic polysilsesquioxane, acrylate and photoinitiator reacting under light can be shown as follows:

[0041]

[0042] Among them, (C6H9O2) n (SiO 1.5 ) n is the chemical formula of acrylic polysilsesquioxane, C3H4O2 is the chemical formula of acrylate, 23 H 30 N2O2 is the chemical formula of DBMP used as a photoinitiator, and R-SiO2 in this formula is used to represent nano-silicon dioxide.

[0043] DBMP incorporated into the polymer matrix forms free radicals through free radical chain polymerization under ultraviolet light, thereby initiating a reaction between acrylic polysilsesquioxane and acrylate.

[0044] Optionally, n can be 8. (C6H9O2)8(SiO 1.5)8, whose Chinese name is acrylic-cage polysilsesquioxane, is a hybrid molecule. The core of acrylic-cage polysilsesquioxane is an inorganic silsesquioxane with organic acryl groups attached to the corners of the cage. Acrylic-cage polysilsesquioxane can be cured by ultraviolet light or electron beam and is suitable for applications requiring scratch resistance and enhanced mechanical properties. Among them, the cage content of acrylic-cage polysilsesquioxane is equal to or greater than 90%.

[0045] In a specific embodiment of the present application, the step of mixing acrylic polysilsesquioxane and acrylic ester and stirring may specifically include: mixing acrylic polysilsesquioxane and acrylic ester in a mass ratio of (5-20):1, and stirring for 5-15 minutes. Acrylic polysilsesquioxane is a component used to provide silicon element in the reaction, and its molecular weight itself is relatively large. Under the premise of obtaining silica glass, acrylic polysilsesquioxane will occupy more mass than acrylic ester in the first mixture, and the molar concentration of acrylic ester is relatively high, which promotes the occurrence of the reaction and improves the utilization rate of acrylic polysilsesquioxane.

[0046] By stirring for 5 to 15 minutes, the acrylic polysilsesquioxane and the acrylate can be fully and evenly mixed, which is beneficial to the subsequent reaction and can improve the efficiency of the reaction.

[0047] Preferably, the stirring time may be 10 minutes. The mass ratio of acrylic polysilsesquioxane to acrylate may be 10:1.

[0048] In a specific embodiment of the present application, the mass ratio of the photoinitiator to the first mixture is 1:(25-100). By setting the mass ratio of the photoinitiator to the first mixture in this embodiment, a sufficient amount of photoinitiator can be provided, so that sufficient free radicals are formed through free radical chain polymerization to improve the efficiency of initiating the reaction between acrylic polysilsesquioxane and acrylate.

[0049] Preferably, the mass ratio of the photoinitiator to the first mixture may be 1:50.

[0050] In a specific embodiment of the present application, the step of adding a photoinitiator to the first mixture and stirring to obtain a glass photoresist may specifically include: adding a photoinitiator to the first mixture in an environment isolated from ultraviolet rays, and stirring for 12 to 24 hours to obtain a glass photoresist.

[0051] Since the photoinitiator can absorb energy of a certain wavelength through ultraviolet light and / or visible light, it can generate free radicals, cations and other compounds that can trigger the monomer to undergo polymerization, cross-linking and curing reactions. Therefore, when performing step S200, the environment can be set to an environment that isolates ultraviolet rays, thereby preventing the photoinitiator from starting to initiate the reaction of acrylic polysilsesquioxane with acrylate too early, thereby reducing the probability of glass photoresist deterioration. Stirring for 12 to 24 hours can make the composition of the glass photoresist more uniform, which can improve the efficiency of obtaining silica glass by the glass photoresist reaction.

[0052] Optionally, the stirring time may be 12 hours.

[0053] Optionally, when the photoinitiator used is capable of generating free radicals, cations and other substances under irradiation in the visible light region, the environment for performing step S200 can be further adjusted to a light-proof environment, thereby reducing the probability of deterioration of the glass photoresist.

[0054] Furthermore, the prepared glass photoresist is not necessarily used immediately, but can be sold as a product. Based on the sales demand, the glass photoresist and its outer packaging need to be transportable and storable, and specifically, the glass photoresist can be contained in containers such as light-proof and sealable hoses and medicine bottles.

[0055] See also Figure 4 , Figure 4 This is a schematic diagram of the second process of the glass photoresist preparation method of the present application. In a specific embodiment of the present application, stirring for 12 to 24 hours to obtain the glass photoresist may specifically include the following steps:

[0056] S201: Heat to 50-70°C and maintain for 6-12 hours with continuous stirring.

[0057] Heating the mixture while stirring can promote the dissolution of the photoinitiator in the first mixture, making the composition of the glass photoresist more uniform, and improving the efficiency of obtaining silica glass by the glass photoresist reaction.

[0058] Preferably, the temperature may be heated to 50° C. and maintained for 6 hours.

[0059] S202: After stopping the heating, stirring is continued for 6 to 12 hours to obtain a glass photoresist.

[0060] The process of cooling the elevated temperature to room temperature can be stirred simultaneously, and stirring can promote heat dissipation.

[0061] Optionally, stirring may be continued for 6 hours after heating is stopped.

[0062] See also Figure 5 , Figure 5This is a schematic flow chart of the femtosecond laser preparation method of the optical fiber end face micro-nano glass structure of the present application. The present application also provides a femtosecond laser preparation method of the optical fiber end face micro-nano glass structure, including:

[0063] S300: Using glass photoresist.

[0064] The glass photoresist can be prepared by using the glass photoresist preparation method described in any of the above embodiments. The glass photoresist may include acrylic polysilsesquioxane and acrylate. Furthermore, it may also include a photoinitiator.

[0065] S400: placing glass photoresist on a preset surface.

[0066] Due to the fluidity of glass photoresist, the glass photoresist can be drop-coated onto a predetermined surface.

[0067] S500: Photocuring the glass photoresist using a photocuring device to form a cured structure of the glass photoresist.

[0068] The photocuring device can specifically be a femtosecond laser device. During the photocuring process, acrylic polysilsesquioxane and acrylate in the glass photoresist react under the action of a photoinitiator to form a cured structure containing silica glass and organic components, which includes a glass monomer polymerization cross-linking structure.

[0069] S600: heat treating the cured structure.

[0070] By heat treating the solidified structure, the organic components in the cross-linked precursor can be effectively decomposed and removed, thereby producing high-quality silica micro-nano glass.

[0071] Through the method provided in this embodiment, an organic-inorganic hybrid glass photoresist different from the traditional silica load can be prepared by a heating mixing method, and the glass photoresist is photocured using a photocuring device, so that the printed cured structure can achieve the printing of a glass monomer polymerization cross-linked structure with a characteristic size exceeding the diffraction limit, thereby improving the accuracy of the glass printing technology. The organic components in the cross-linked precursor can be effectively decomposed through heat treatment, thereby realizing the manufacture of high-quality silica micro-nano glass.

[0072] In a specific embodiment of the present application, the step S400 of disposing glass photoresist on a preset surface may include: disposing glass photoresist on an end face of an optical fiber.

[0073] The femtosecond laser preparation method of the micro-nano glass structure on the end face of an optical fiber can be applied to the end face of an optical fiber to prepare a glass micro-cantilever beam on the end face of the optical fiber, and can make it have good high-temperature stability. The existing silica additive printing technology is difficult to be applied to the end face of an optical fiber due to the size of silica nanoparticles and the sintering temperature problem. The femtosecond laser preparation method of the micro-nano glass structure on the end face of an optical fiber improved by the embodiment of the present application can perform high-precision printing on the end face of the optical fiber, thereby meeting the needs of users.

[0074] The step S500 of photocuring the glass photoresist using a photocuring device may include: photocuring the glass photoresist using a femtosecond laser device, wherein the power of the femtosecond laser is less than or equal to 5 mW.

[0075] By controlling the power of the femtosecond laser, a solidified structure that meets the precision requirements can be printed. The greater the power of the femtosecond laser, the thicker the lines printed by the photocuring, and thick lines are not conducive to forming fine structures. Therefore, the correlation between the power of the femtosecond laser and the precision can be that the precision decreases as the power of the femtosecond laser increases.

[0076] Among them, when the working power of the femtosecond laser is set to below 5mW, the structure with line thickness below 100nm can be printed using glass photoresist, and the printing of glass monomer polymerization cross-linked structure with characteristic size beyond the diffraction limit (line width 100nm) can be achieved.

[0077] See also Figure 6 , Figure 6 It is a schematic flowchart of the heat treatment process of the femtosecond laser preparation method of the optical fiber end face micro-nano glass structure of the present application.

[0078] In a specific embodiment of the present application, the step S600 of heat treating the solidified structure may include the following steps:

[0079] S601: raising the temperature of the solidified structure to 600-800° C. at a rate of 1-3° C. / min, and maintaining the temperature for 1-3 hours.

[0080] Heating the solidified structure to 600-800°C can effectively promote the decomposition of organic components in the cross-linked precursor, thereby producing high-quality silica micro-nano glass based on the solidified structure.

[0081] Preferably, the temperature of the cured structure may be raised to 700° C. The heating rate may be 2° C. / min and the constant temperature time may be 1 hour.

[0082] S602: Cool the solidified structure to room temperature at a rate of 3-7°C / min.

[0083] During the heat treatment of the solidified structure, the heating rate can be controlled by using a tubular furnace, and the solidified structure can be slowly heated and cooled to avoid structural damage caused by uneven heat transfer due to too fast a heating rate, thereby improving the quality of the prepared silica micro-nano glass and improving the stability of the femtosecond laser preparation method of the micro-nano glass structure on the end face of the optical fiber.

[0084] Preferably, the cooling rate may be 5°C / min.

[0085] In a specific embodiment of the present application, after the glass photoresist is formed into a solidified structure in step S500 and before the solidified structure is heat-treated in step S600, the step further includes washing the preset surface with isopropyl alcohol.

[0086] Isopropyl alcohol can be used to wash the preset surface of the solidified structure, so that the uncured resin on the preset surface and the solidified structure can be removed by the principle of like dissolves like, and the excess part can be removed to form a high-precision solidified structure.

[0087] Optionally, the duration of washing the preset surface with isopropyl tone may be 2 to 5 minutes. Preferably, the duration of washing the preset surface with isopropyl tone may be 3 minutes.

[0088] According to the technical features provided in this application, the specific implementation method of the femtosecond laser preparation method of the optical fiber end face micro-nano glass structure can be as follows:

[0089] (1) Preparation of glass photoresist: 1-2 g acrylic polysilsesquioxane is mixed with 100-200 mg acrylic ester monomer, and stirred evenly for 5-15 minutes. 22-44 mg photoinitiator is added in a UV protection environment, heated at 50-70° C. and stirred for 6-12 hours, and cooled at room temperature and stirred for 6-12 hours to fully dissolve the photoinitiator.

[0090] (2) 3D printing of glass glue structure on the fiber end face: drop glass glue on the fiber end face, process it with femtosecond laser, dissolve the remaining uncured resin in isopropyl alcohol (3-5 minutes) and dry it in air.

[0091] (3) Heat treatment: Heat in a tubular furnace at a heating rate of 1 to 3 °C / min to 700 °C and keep the temperature constant for 1 to 2 hours, then cool at a cooling rate of 3 to 7 °C / min.

[0092] Example:

[0093] Example 1

[0094] (1) Preparation of glass photoresist: 1 g of acrylic polysilsesquioxane was mixed with 100 g of acrylate monomer, and the mixture was stirred evenly for 10 minutes. 2 g of photoinitiator was added in a UV-protected environment, and the mixture was heated at 50° C. and stirred for 6 hours. The mixture was cooled at room temperature and stirred for 6 hours to fully dissolve the photoinitiator. Finally, the mixture was cooled to room temperature.

[0095] (2) 3D printing of glass glue structure on the fiber end face: drop glass glue on the fiber end face, process it with femtosecond laser (power 5 mW), dissolve the remaining uncured resin in isopropyl alcohol (3 minutes) and dry it in air.

[0096] (3) Heat treatment: Heating in a tubular furnace, heating to 700°C at a rate of 2°C / min and keeping the temperature constant for 1 hour, and then cooling at a rate of 5°C / min.

[0097] Example 2

[0098] (1) Preparation of glass photoresist: 1 g of acrylic polysilsesquioxane was mixed with 100 mg of acrylate monomer, and the mixture was stirred evenly for 10 minutes. 22 mg of photoinitiator was added in a UV protection environment, and the mixture was heated at 50° C. and stirred for 6 hours. The mixture was cooled at room temperature and stirred for 6 hours to fully dissolve the photoinitiator. Finally, the mixture was cooled to room temperature.

[0099] (2) 3D printing of glass glue structure on the fiber end face: drop glass glue on the fiber end face, process it with femtosecond laser (power 6 mW), dissolve the remaining uncured resin in isopropyl alcohol (3 minutes) and dry it in air.

[0100] (3) Heat treatment: Heating in a tubular furnace, heating to 700°C at a rate of 2°C / min and keeping the temperature constant for 1 hour, and then cooling at a rate of 5°C / min.

[0101] Example 3

[0102] (1) Preparation of glass photoresist: 1 g of acrylic polysilsesquioxane was mixed with 100 mg of acrylate monomer, and the mixture was stirred evenly for 10 minutes. 22 mg of photoinitiator was added in a UV protection environment, and the mixture was heated at 50° C. and stirred for 6 hours. The mixture was cooled at room temperature and stirred for 6 hours to fully dissolve the photoinitiator. Finally, the mixture was cooled to room temperature.

[0103] (2) 3D printing of glass glue structure on the fiber end face: glass glue was dropped on the fiber end face and processed by femtosecond laser (power 7 mW). The remaining uncured resin was dissolved in isopropyl alcohol (3 minutes) and dried in air.

[0104] (3) Heat treatment: Heating in a tubular furnace, heating to 700°C at a rate of 2°C / min and keeping the temperature constant for 1 hour, and then cooling at a rate of 5°C / min.

[0105] Example 4

[0106] (1) Preparation of glass photoresist: 1 g of acrylic polysilsesquioxane was mixed with 100 mg of acrylate monomer, and the mixture was stirred evenly for 10 minutes. 22 mg of photoinitiator was added in a UV protection environment, and the mixture was heated at 50° C. and stirred for 6 hours. The mixture was cooled at room temperature and stirred for 6 hours to fully dissolve the photoinitiator. Finally, the mixture was cooled to room temperature.

[0107] (2) 3D printing of glass glue structure on the fiber end face: drop glass glue on the fiber end face, process it with femtosecond laser (power 8 mW), dissolve the remaining uncured resin in isopropyl alcohol (3 minutes) and dry it in air.

[0108] (3) Heat treatment: Heating in a tubular furnace, heating to 700°C at a rate of 2°C / min and keeping the temperature constant for 1 hour, and then cooling at a rate of 5°C / min.

[0109] Example 5

[0110] (1) Preparation of glass photoresist: 1 g of acrylic polysilsesquioxane was mixed with 100 mg of acrylate monomer, and the mixture was stirred evenly for 10 minutes. 22 mg of photoinitiator was added in a UV protection environment, and the mixture was heated at 50° C. and stirred for 6 hours. The mixture was cooled at room temperature and stirred for 6 hours to fully dissolve the photoinitiator. Finally, the mixture was cooled to room temperature.

[0111] (2) 3D printing of glass glue structure on the fiber end face: glass glue was dropped on the fiber end face, processed by femtosecond laser (power 9 mW), and the remaining uncured resin was dissolved in isopropyl alcohol (3 minutes) and dried in air.

[0112] (3) Heat treatment: Heating in a tubular furnace, heating to 700°C at a rate of 2°C / min and keeping the temperature constant for 1 hour, and then cooling at a rate of 5°C / min.

[0113] Test print on glass photoresist:

[0114] The femtosecond laser used in the test is a titanium sapphire laser produced by Coherent, model Astrella, with a central wavelength of 800nm, a pulse width of 35fs, a repetition frequency of up to 1000Hz, a maximum single pulse energy of 7mJ, and a Gaussian light intensity distribution. The printing method adopts two-photon printing, and nanowires are printed on the substrate according to the methods and parameters described in Examples 1 to 5. Each example is repeated twice, and nanowires of different widths can be obtained, such as Figure 1 As shown, Figure 1 The electron microscope images of multiple embodiments of the femtosecond laser preparation method for the micro-nano glass structure on the end face of an optical fiber of the present application are shown in FIG. The width of the nanowires can reflect the minimum size of the solidified structure printed by the femtosecond laser preparation method for the micro-nano glass structure on the end face of an optical fiber, thereby reflecting the accuracy of the femtosecond laser preparation method for the micro-nano glass structure on the end face of an optical fiber.

[0115] Among them, the working principle of common 3D printers is layered manufacturing, which limits the accuracy between layers and creates the so-called "step effect", which seriously affects the manufacturing accuracy. Two-photon printing is based on the "two-photon absorption effect". By focusing the laser, the photocuring reaction area can be localized to a very small position near the focus. Two-photon printing uses a nano-scale precision moving stage to move the focus within the photosensitive material. The photosensitive material denatures and solidifies at the position where the focus passes. Through two-photon printing, the accuracy of 3D printing can be improved to the micro-nano scale.

[0116] for Figure 1 The width of the nanowires was measured, and the average value of the two nanowires in each embodiment was taken and recorded in Table 1, which is shown below.

[0117] Table 1 Relationship between printing power and line width

[0118] serial number Example 1 Example 2 Example 3 Example 4 Example 5 power 5mW 6mW 7mW 8mW 9mW Line Width 82nm 108nm 128nm 153nm 182nm

[0119] According to the data shown in Table 1, Figure 1 By comparing the nanowires in the figure, we can find the correlation between the power of the femtosecond laser and the width of the nanowires. The higher the power of the femtosecond laser, the wider the nanowires, and the lower the precision of the solidified structure obtained by the femtosecond laser preparation method of the corresponding optical fiber end face micro-nano glass structure.

[0120] High temperature stability testing of cured structures:

[0121] The method in Example 1 is used to print a solidified structure on the end face of the optical fiber. The solidified structure is placed in a tube furnace and heated to 900°C for 5 hours. The reflection spectrum wavelength of the solidified structure is monitored by a spectrometer. The statistical graph made using the reflection spectrum wavelength is shown in FIG. Figure 2 As shown, Figure 2 This is a structural statistical diagram of the high temperature stability test of the solidified structure obtained by the femtosecond laser preparation method of the optical fiber end face micro-nano glass structure of the present application. The data of the reflection spectrum wavelength at different times are recorded in Table 2, which is shown below.

[0122] Table 2 Relationship between high temperature treatment time and wavelength

[0123] Time (minutes) 0 50 100 150 200 250 300 Wavelength (nm) 1383 1383 1384 1384 1384 1384 1384

[0124] pass Figure 2It can be found from the data in Table 2 that as time goes by, the wavelength of the reflection spectrum is always maintained at 1383-1384 nm in the range of 0-300 minutes, which is a relatively stable level. Moreover, 900°C is higher than 600-700°C for heat treatment of the cured structure, which proves that the silica micro-nano glass structure prepared by the embodiment of the present application has good high temperature stability, and the temperature of heat treatment does not have an adverse effect on the performance of the silica micro-nano glass on the optical fiber and the end face of the optical fiber.

[0125] The above is only a specific implementation method of the present application. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present application. These improvements and modifications should also be regarded as the scope of protection of the present application.

Claims

1. A glass photoresist, characterized in that: Includes acrylic polysilsesquioxane, acrylate.

2. A method for preparing a glass photoresist, characterized in that: For preparing the glass photoresist as claimed in claim 1, comprising: Mixing acrylic polysilsesquioxane and acrylate and stirring to obtain a first mixture; A photoinitiator is added to the first mixture, and the mixture is stirred to obtain the glass photoresist.

3. The method for preparing glass photoresist according to claim 2, characterized in that: The mixing of acrylic polysilsesquioxane and acrylate and stirring comprises: Mix acrylic polysilsesquioxane and acrylic ester in a mass ratio of (5-20):1, and stir for 5-15 minutes.

4. The method for preparing glass photoresist according to claim 2, characterized in that: The mass ratio of the photoinitiator to the first mixture is 1:(25-100).

5. The method for preparing glass photoresist according to claim 2, characterized in that: The step of adding a photoinitiator to the first mixture and stirring to obtain the glass photoresist comprises: The photoinitiator is added to the first mixture in an environment isolated from ultraviolet rays, and the mixture is stirred for 12 to 24 hours to obtain the glass photoresist.

6. The method for preparing glass photoresist according to claim 5, characterized in that: The stirring for 12 to 24 hours to obtain the glass photoresist comprises: Heat to 50-70°C and maintain for 6-12 hours, stirring continuously; After stopping the heating, stirring is continued for 6 to 12 hours to obtain the glass photoresist.

7. A femtosecond laser preparation method for a micro-nano glass structure at the end face of an optical fiber, characterized in that: include: Using the glass photoresist as claimed in claim 1; placing the glass photoresist on a preset surface; Using a photocuring device to photocuring the glass photoresist so that the glass photoresist forms a cured structure; The cured structure is heat treated.

8. The femtosecond laser preparation method of the optical fiber end face micro-nano glass structure according to claim 7, characterized in that: The step of arranging the glass photoresist on a preset surface comprises: placing the glass photoresist on the end face of the optical fiber; The photocuring of the glass photoresist by using a photocuring device comprises: The glass photoresist is photocured by using a femtosecond laser device, wherein the power of the femtosecond laser is less than or equal to 5 mW.

9. The femtosecond laser preparation method of the optical fiber end face micro-nano glass structure according to claim 7, characterized in that: The heat treatment of the solidified structure comprises: The solidified structure is heated to 600-800° C. at a rate of 1-3° C. / min and kept at the constant temperature for 1-3 hours; The solidified structure is cooled to room temperature at a rate of 3-7°C / min.

10. The femtosecond laser preparation method of the optical fiber end face micro-nano glass structure according to claim 7, characterized in that: After forming the glass photoresist into a solidified structure and before heat treating the solidified structure, the method further comprises: The predetermined surface is cleaned with isopropyl alcohol.

Citation Information

Cited By

  • High-transparency rare earth nanoparticle / polyhedral oligomeric silsesquioxane composite photoresist as well as preparation method and application thereof

    CN121806380A

  • Highly transparent rare earth nanoparticle / caged polysilsesquioxane composite photoresist, and preparation method and application thereof

    CN121806380B